Textile-Reinforced Mortar (TRM) Strengthened One-Way Reinforced Concrete Slabs - Amenah S. Dheyab; Saad M. Raoof (Tikrit Journal of Engineering Sciences, 2021)
The issue of upgrading and strengthening the reinforced concrete (RC) infrastructure has become of great importance. Recently, textile-reinforced mortar (TRM) was used in the field of structural strengthening. In the current study, using of TRM for flexural retrofitting of one-way reinforced concrete (RC) slabs was experimentally and theoretically investigated. The parameters examined included; the number of TRM layers (1, 3, 5 layers) and the strengthening configuration fully and partially). For this purpose, eight specimens were prepared and tested under three points- loading up to failure. The result showed that the TRM increases substantially the flexural capacity of RC slabs. The highest flexural capacity increase recorded was 103 %. It was also noted that increasing the number of retrofitting layers resulted in different increases in the flexural capacity. It was also shown that the strengthening configuration plays an important role in the effectiveness of the technique. The fully covered approach showed higher loading capacity than the partial cover technique provided that the same TRM layer is applied. Finally, the ultimate moment of the strengthened specimens was calculated theoretically and compared with that obtained experimentally. The results of calculations showed a good agreement between the theoretical and experimental results.